2023
DOI: 10.1128/msystems.00415-23
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium butyrate facilitates CRHR2 expression to alleviate HPA axis hyperactivity in autism-like rats induced by prenatal lipopolysaccharides through histone deacetylase inhibition

Abstract: Short-chain fatty acids (SCFAs, especially butyric acid) have been demonstrated to play a promising role in the development of autism spectrum disorders (ASD). Recently, the hypothalamic–pituitary–adrenal (HPA) axis is also suggested to increase the risk of ASD. However, the mechanism underlying SCFAs and HPA axis in ASD development remains unknown. Here, we show that children with ASD exhibited lower SCFA concentrations and higher cortisol levels, which were recaptured in prenatal lipopolysaccharide (LPS)-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…The membrane was washed 3 × 5 min in TBS‐T and then incubated in either rabbit anti‐OTR (1:300, Abcam (Waltham, MA, USA), ab217212, overnight, ) or rabbit anti‐CRHR2 (1:1000, Abcam, ab236982, 3 nights) antibodies in TBS‐T with 5% milk at 4°C on a shaker. Antibody specificity has been previously confirmed (Wang et al., 2023; Wei et al., 2023). Following a TBS‐T wash (3 × 5 min) the membrane was incubated in donkey anti‐rabbit antibody conjugated to peroxidase (1:5000, Jackson ImmunoResearch) for 2 h on a shaker at room temperature.…”
Section: Methodsmentioning
confidence: 70%
“…The membrane was washed 3 × 5 min in TBS‐T and then incubated in either rabbit anti‐OTR (1:300, Abcam (Waltham, MA, USA), ab217212, overnight, ) or rabbit anti‐CRHR2 (1:1000, Abcam, ab236982, 3 nights) antibodies in TBS‐T with 5% milk at 4°C on a shaker. Antibody specificity has been previously confirmed (Wang et al., 2023; Wei et al., 2023). Following a TBS‐T wash (3 × 5 min) the membrane was incubated in donkey anti‐rabbit antibody conjugated to peroxidase (1:5000, Jackson ImmunoResearch) for 2 h on a shaker at room temperature.…”
Section: Methodsmentioning
confidence: 70%
“…In addition, recently, increased activation of the HPA axis was suggested to play an important role in ASD-like social behaviors ( Jacobson, 2014 ; Rusch et al, 2023 ). As CRHR2 is one of the receptors for the hormones involved in the HPA axis, decreased CRHR2 expression levels in the hypothalamus were recently suggested to increase the risk of ASD ( Wang X. et al, 2023 ). Interestingly, the current data revealed that an intronic CRHR2 variant (rs7793837), which mostly causes mutations in the CRHR2 protein, was significantly associated with a positive impact on the total active moiety level in the plasma of children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Increased Urocortin"s after chronic variable stress is in accordance with the findings of [ 26 , 27 ] where stress induces neurodegenerative process with in the limbic system and hippocampus which causes more detrimental effects by high production of glucocorticoids which leads to the production of free radicals in the neurons because of oxidative stress [ 26 , 27 ]. It has been postulated that glucocorticoids regulate CRF transcription via a cAMP-responsive element (CRE) present in the promoter of the CRF-gene [ 28 ] Since CRE is also present in the promoter of the mouse UCN1 gene it might be a target for glucocorticoids to regulate UCN1-gene expression [ 29 ]. On the other hand, the expression of UCN2 in the mouse hypothalamus and brainstem appears to be controlled by glucocorticoids via a glucocorticoid-responsive element (GRE) in the Ucn2-gene promoter were reported [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%